Phytochemical and Anti-Anaemic Properties of Ethanol Leaf Extract of Justicia carneaVahl (Acantheceae) - Igbinaduwa, Patrick O.; Kabari, Kosa Maureen; Chikwue, Thelma C. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
Justicia carnea is a medicinal plant reported to have diverse pharmacological functions, including blood-boosting potentials. The study investigated the phytochemical, proximate parameters as well as the effects of the ethanol extract of Justicia carnea (JC) leaves in phenylhydrazine induced-anemia in albino rats were investigated. Quantitative phytochemical screening and proximate analyses were carried out using standard methods. The experimental animals were randomly grouped into six groups of three rats each – group 1 (non-anemic control), group 2 (anemic control), group 3 (100 mg/kg of JC extract), group 4 (200 mg/kg of JC extract), group 5 (500 mg/kg) and group 6 (1000 mg/kg). Phenylhydrazine was administered once a day at the dose of 10mg/kg to induce aneamia. After 7 days of administration, animals were sacrificed.Serum was collectedfor biochemical analysis and organs harvested for histopathological analysis. Quantitative phytochemical analysis showed the presence of secondary metabolites such as saponins (2.50 mg/100g), tannins (2.16 mg/100g), alkaloids (1.88 mg/100g). Saponins were the most abundant secondary metabolites while flavonoids (0.08%) were in minute quantity. Calcium (1930?) and potassium (14800?) were the most abundant minerals in the aqueous extract of the leaf while zinc (73?) was present in low concentration and lead (1.0?) in minute quantity. Packed cell volume (PCV), red blood cell (RBC), platelet concentration and hemoglobin (Hb) concentrations decreased significantly after 4 days of phenylhydrazine induction, but after 7 days of administering extracts of Justicia carnea, PCV values, RBC, platelet and Hb increased significantly. Other components of the blood such as eosinophil, basophil, monocytes, and lymphocytes also showed positive improvement. Ethanol leaf extract of Justicia carnea reversed phenylhydrazine induced anemia in the treated animals. This study validates the ethnomedicinal use of the plant as a traditional blood supplement in the management of anemia.